Study of organic pollution indicators in two stations of the Garmat Ali River, Basra, Iraq - Ahmed, Mayada H.; Abdullah, Abdulaziz M.; Nasir, Noori AN. (Iraqi Journal of Aquaculture, 2023)
Water is one of the most important natural sources for sustaining life, as human life and various activities depend on it. The current study dealt with knowing the effect of organic pollution on physical and chemical properties in Garmat Ali river, which was represented in two stations, the first station called Al-Mashab, and the second Al-Sindbad. Water and sediment samples were collected monthly during the period from August, 2016 to July, 2017. Numbers of physical and chemical variables were measured during this period (water temperature, light penetration, pH, Salinity, dissolved oxygen, biological demand oxygen, chemical demand oxygen, total nitrogen, total phosphorus and total organic carbon in sediment). The results of the study was showed that water temperature were ranged between 13.2-31.3°C for the first station and 13.4-33.1°C for the second station. The light penetration values were ​​ranged between 20.6-58.5 cm for the first station and 35-65 cm for the second station. The pH values were ​​ranged between 7.5-8.6 for the first station and 7.5-8.5 for the second station. Salinity values were ​​ranged between 1.58-3.16 g/l for the first station and 0.92-2.13 g/l for the second station. Dissolved oxygen values were ​​ranged between 4.66-10.8 mg/l for the first station and 11.85-6.26 mg/l for the second station. The values ​​of BOD5 were ​​ranged between 1.1-4.26 mg/l for the first station and 0.75-4.06 mg/l for the station. The values ​​of the COD were ranged between 8-120 mg/l for the first station and 8-61 mg/l for the second station. Total nitrogen values were ​​ranged between 2.8-29.4 mg/l for the first station and 2.4-33.6 mg/l for the second station. The total phosphorus values were ​​ranged between 1.11-19.6 mg/l for the first station and between 1.24-19.98 mg/l for the second station. Total organic carbon values were ​​ranged between 0.36-2.19% for the first station and 0.32-2.94% for the second station. The two stations were recorded a little increased in organic pollution levels during summer months and first station (Al-Mashab) was most affected.